Bartok the Magnificent [videorecording (DVD)] - Bluth, Don; Goldman, Gary; Ahrens, Lynn; Flaherty, Stephen; Azaria, Hank, 1964- (Twentieth Century Fox Home Entertainment, 1999)
When young Prince Ivan is kidnapped, Bartok the bat must rescue him.